Effictiveness of Word Square Learning Model on Learning Outcomes of Al-Qur’an Hadith in Islamic Elementary Education - Dewi Puji Badi'ul Fitriyah (Journal of Elementary Education Research and Practice, 2025)
This study uses a quantitative approach with a pre-experimental type with a One-Group Pretest-Posttest Design, aiming to find out whether or not there is an effect on the difference in learning outcomes of the Qur'an Hadith of students before using and after using the word square learning model. The data collection technique was carried out using the results of the pretest and posttest tests in the form of multiple choice. Sampling was carried out using a purposive sampling technique involving 30 students. Based on the results of data analysis, it shows that the average value of learning outcomes of the Qur'an Hadith (68.33<80.50). The results of the t test show that t tcounts > ttable (4.134 > 2.045), with a significance level of 0.05 (0.000< 0.05). This shows that there is an influence of the use of the word square learning model on the learning outcomes of the Qur'an Hadith of students.